PENGARUH REVIEW CONTENT CREATOR DAVID GADGETIN PALTFORM YOUTUBE TERHADAP MINAT BELI PADA PRODUK SMARTPHONE DI KOTA TANJUNGPINANG - Fauzar, Selvi; Haryani, Dwi Septi; Ratnasari, Sri Langgeng; Susanti, Ervin Nora; Fenny, Fenny (STIE PEMBANGUNAN TANJUNGPINANG, 2025)
The development of social media, especially Instagram and YouTube, has changed the way people choose products, particularly smartphones. Content creators like David Gadgetin had a significant influence on consumer purchasing decisions. Their reviews were considered an important reference in selecting the right product. This study aimed to examine how the reviews of content creator David Gadgetin on YouTube influenced purchasing interest in smartphone products. The method used was quantitative research. The study involved 400 respondents who actively followed product reviews on David Gadgetin's YouTube channel. Data were collected through a validated questionnaire and analyzed using relevant statistical methods, specifically simple linear regression with the data processing software JASP 0.19.0.0 (2024). The results of this study indicate that Reviews have a positive and significant influence on Purchase Interest, where the calculated t value> t table (29.716> 1.966) with prob. Sig <0.05 (<0.001 <0.05). Based on these results, it can be concluded that overall, Reviews have an influence on purchase interest on David Gadgetin's YouTube channel. This confirms that reviews are an important factor in increasing purchase interest. It can be concluded that reviews have a partial positive effect on buying interest. Based on the results of this research, it is also concluded that improving the quality of reviews can significantly increase consumer buying interest, which means that the reviews contained in buying interest are included in the good category.